Exploring Undergraduate Students’ Perspectives on the Integration of Podcasts for Enhancing Listening Skills - Andriani, Agis; Pertamana, Dede; Novianti, Litany Tiara (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
Podcasts have gained popularity among a vast number of listeners who utilize them to enhance their English listening skills. However, limited classroom time is allocated for focused listening practice. This research aims to investigate students’ perceptions of using podcasts as an effective means of improving their listening abilities. Three participants volunteered to take part in the study, and additional recruitment efforts were made to encourage more student volunteers. Semi-structured interviews were conducted to gather data, allowing for the exploration of individual experiences, attitudes, perceptions, and beliefs related to the use of podcasts. Four key themes emerged from the participants’ perceptions: 1) Hearing the message, 2) Interpreting the message, 3) Evaluating the message, and 4) Responding to the message. Listening involves interpreting the communicative behavior of others to comprehend its meaning, and effective listeners ensure they have all the necessary information before forming opinions. The findings indicate that podcasts facilitate clear message reception, provide verbal and non-verbal cues for deeper interpretation, offer features to optimize the listening process, and provide an authentic experience of listening to native speakers. Future research is recommended to explore students’ perceptions of using podcasts for improving other English language skills.